The Blue Ribbon Panel on Depowered and Advanced Airbags — Status Report on Airbag Performance - Ferguson, Susan A. (Association for the Advancement of Automotive Medicine, 2003)
In February 2000, a group of highway safety organizations sent a letter to the Secretary of the U.S. Department of Transportation expressing concern about a possible return to the 30-mph rigid barrier test using unbelted dummies previously required by Federal Motor Vehicle Safety Standard (FMVSS) 208. The letter asked the National Highway Traffic Safety Administration (NHTSA) to expedite data collection of the real-world crash experience of airbag-equipped vehicles certified to the 30-mph sled test using unbelted dummies because of suggestions that depowered airbags may not provide the same level of protection, particularly to larger, unbelted occupants. For the same reason, the letter also recommended that the auto industry commit funding for additional data collection and to establish a panel of experts to evaluate the data. In response, the Alliance of Automobile Manufacturers (Alliance) committed to funding a 3-year program to be managed by an independent third party. A panel of experts consisting of representatives from the highway safety research community, the National Transportation Safety Board, academia, medical institutions, and the insurance industry was established as the Blue Ribbon Panel (BRP) for Evaluation of Depowered and Advanced Airbags and met for the first time in February 2001. The BRP also includes representatives from NHTSA and the automobile industry who participate as observers. The BRP held its first public meeting in April 2003 to provide an update of its activities and to summarize the real-world evidence on the performance of depowered airbags. This AAAM session will provide a brief summary of the public meeting.